THE GREEN PLACE BUILDING FOR LOOKING BIRD AT GUANGZHOU NANSHA BIRD PARK (INFINITE 8) - Fariz Nizar; Naufal Kresna Diwangkara (Merdeka Indonesia Jurnal International, 2022)
This research is located in the Nansha Bird Park located in Guangzhou which has an unspoiled wetland landscape. we designed the building with the concept of